Impacts of the subsurface storage of natural gas and hydrogen mixtures. (18th March 2020) - Shi, Zhuofan; Jessen, Kristian; Tsotsis, Theodore T.
Abstract: The subsurface storage of hydrogen (H2 ) provides a potential solution for load-balancing of the intermittent electricity production from renewable energy sources. In such technical concept, surplus electricity is used to power electrolyzers that produce H2, which is then stored in subsurface formations to be used at times when renewable electricity is not available. Blending H2 with natural gas (NG) for injection into depleted gas/oil reservoirs, which are already used for NG storage, is considered a good option due to the lower initial capital cost and investment needed, and potential lower operating costs. In this study, the potential impact of storing a mixture of H2 and NG in an existing NG storage field was investigated. Relevant reservoir, caprock and cement samples from a NG storage formation in California were characterized with respect to their permeability, porosity, surface area, mineralogy and other structural characteristics, before and after undergoing 3-month incubation experiments with H2 /NG gas mixtures at relevant temperature and pressure conditions. The results indicated relatively small changes in porosity and mineralogy due to incubation. However, the observed changes in permeability were more dramatic. In addition, polymeric materials, similar to those used in NG storage operations were also incubated, and their dimensions were measured before and after incubation. These measurements indicated swelling due to the exposure to H2 . However, direct evidence of geochemical reactions involving H2 was not observed. Graphical abstract: Image 1 Highlights: Impact of storing a mixture of H2 and natural gas (NG) in an existing storage field. Reservoir rock, caprock and cement samples from an active NG storage operation. 3-month incubation with H2 /NG gas mixtures at relevant T and p conditions. Changes in minerology are modest while changes in permeability are more dramatic. Significant swelling of polymerics gasket materials was observed.